A Project Report on Internet/Lan Enabled Smart Home - ARCHANA B G, KHANINDRA DAS, MEHABOOB SUBHAN and NARENDRA BABU (2008)
INTERNAL GUIDE: VIMALA D , MVJCE EXTERNAL GUIDE: SHAILENDRA, APSIS SOLUTIONS
Keywords: Internet/Lan Enabled Smart Home